2023
DOI: 10.1177/00315125231167460
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Sport Satisfaction and Perceived Self-Efficacy Among Youth in a Competitive Environment

Abstract: Young people’s sources of satisfaction in sport are an important indicator of their long-term sport participation. Contextual factors and an individual’s internal dispositions act synergistically to determine a positive experience. We studied sources of sport satisfaction and perceived self-efficacy of 1,151 male and female youth athletes ( M age = 14.72, SD = 1.56 years) in Brazil who were engaged in school state level competition. The participants responded to questionnaires on their sport satisfaction and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…They also reported that feedback and encouragement from teachers/coaches were vital in maintaining motivation and pushed them to work hard, which enabled success and belief in their abilities. This relationship is also reported as a source for efficacy by Reverdito et al (2023) with regard to young individuals engaged in sports. As highlighted above, PE teachers and coaches were also key to the provision of positive experiences where students had opportunities to teach others, such as leading small group activities with lower-grade groups.…”
Section: Discussionmentioning
confidence: 85%
“…They also reported that feedback and encouragement from teachers/coaches were vital in maintaining motivation and pushed them to work hard, which enabled success and belief in their abilities. This relationship is also reported as a source for efficacy by Reverdito et al (2023) with regard to young individuals engaged in sports. As highlighted above, PE teachers and coaches were also key to the provision of positive experiences where students had opportunities to teach others, such as leading small group activities with lower-grade groups.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, the concept of the sports self-confidence is based on the theory of self-efficacy with an effort to better capture the context of the competitive sports [45,49]. The term sports self-confidence is then defined as an individual's belief in his ability to succeed in sports [45,50].…”
Section: Sport Self-confidencementioning
confidence: 99%
“…A participação e formação esportiva representa uma área de dinâmica complexa, sendo a chave para o bom desenvolvimento do praticante de esporte comumente inferida a qualidade das relações, engajamento, cenários apropriados, suporte familiar e oferta de experiências formativas adequadas no longo prazo (Ivarsson et al, 2015;Côté, Turnnidge, Vierimaa, Evans & Galatti, 2017;Sullivan, Woods, Vaughan & Davids, 2021;Machado et al, 2021;Pramdhan, Santosa, Supriadi & Karisman, 2022;Sweeney, Horan & Macnamara, 2022;Reverdito et al, 2023). Nos últimos anos, há um debate crescente a respeito da formação de futebolistas, sustentado pela busca por maximizar os sistemas de participação e formação de novos praticantes da modalidade (Ford et al, 2012;Machado et al, 2021;Sweeney et al, 2022).…”
Section: Introductionunclassified